Transforaminal interbody debridement and fusion with antibiotic-impregnated bone graft to treat pyogenic discitis and vertebral osteomyelitis: a comparative study in Asian population - Chao-Chien Chang; Hsiao-Kang Chang; Meng-Ling Lu; Adam Wegner; Re-Wen Wu; Tsung-Cheng Yin (Asian Spine Journal)
Study Design A retrospective cohort study. Purpose To evaluate whether using antibiotic-impregnated bone graft (AIBG) enhances infection control and shortens the postoperative course of pyogenic discitis and vertebral osteomyelitis (PDVO). Overview of Literature Surgical treatment of PDVO is indicated for neurological deficit, instability, unknown pathogen, or poorly controlled infection. The posterior-only approach is effective but requires 4–6 weeks of antibiotic treatment postoperatively. We hypothesized that AIBG used in an all-posterior approach could enhance infection control and shorten the postoperative course of PDVO. Methods Thirty patients with PDVO of the lumbar or thoracic spine treated with transforaminal interbody debridement and fusion (TIDF) with AIBG between March 2014 and May 2022 were reviewed (AIBG group). For comparative analysis, 28 PDVO patients who underwent TIDF without AIBG between January 2009 and June 2011 were enrolled (non-AIBG group). The minimum follow-up duration was 2 years. Clinical characteristics and surgical indications were comparable in the two groups. C-reactive protein (CRP) levels and the postoperative antibiotics course were compared between the two groups. Results Surgical treatment for PDVO resulted in clinical improvement and adequate infection control. Despite the shorter postoperative intravenous antibiotic duration (mean: 19.0 days vs. 39.8 days), the AIBG group had significantly lower CRP levels at postoperative 4 and 6 weeks. The mean Visual Analog Scale pain scores improved from 7.3 preoperatively to 2.2 at 6 weeks postoperatively. The average angle correction at the last follow-up was 7.9°. Conclusions TIDF with AIBG for PDVO can achieve local infection control with a faster reduction in CRP levels, leading to a shorter antibiotic duration.